Perceived Facilitators and Barriers to Treatment Fidelity in Computerized Cognitive Training Interventions. Issue 3 (20th May 2023) - Algashgari, Elham Y.; Jung, Miyeon; Von Ah, Diane; Stewart, Jesse C.; Pressler, Susan J.
Abstract : Background: Computerized cognitive training (CCT) interventions may have an important role in improving cognition among patients with heart failure. Ensuring treatment fidelity of CCT interventions is an essential part of testing their efficacy. Objective: The aim of this study was to describe facilitators of and barriers to treatment fidelity perceived by CCT intervenors while delivering the interventions to patients with heart failure. Methods and Results: A qualitative descriptive study was completed with 7 intervenors who delivered CCT interventions in 3 studies. Directed content analysis revealed 4 main themes of perceived facilitators: (1) training for intervention delivery, (2) supportive work environment, (3) prespecified implementation guide, and (4) confidence and awareness. Three main themes were identified as perceived barriers: (1) technical issues, (2) logistic barriers, and (3) sample characteristics. Conclusion: This study is novel because it was one of the few studies focused on the intervenors' perceptions rather than the patients' perception of using CCT interventions. Beyond the treatment fidelity recommendations, this study found new components that might help the future investigators in designing and implementing CCT interventions with high treatment fidelity.